Laboratory Detection of Covid19 Cases: A Systematic Review (Bangladesh Journal of Infectious Diseases, 2020)
Background: The world is struggling to contain the novel coronavirus (COVID-19) outbreak and the healthcare infrastructure and testing capacity have emerged as major issues. Adequate testing capacity for SARS-CoV-2 is lacking worldwide, preventing people from accessing care. It also means the community is relying on models and estimates to get an accurate picture of the outbreak and its evolution, even though this information is critical to inform public health measures that could stop or slow diseases transmission. Different countries have implemented different testing strategies, reflecting the availability of diagnostics and reagents and the needs of the individual health systems.Objective: The purpose of the present study was to see the different laboratory tests for detection of SARS Cov2 from Covid19 patients.Methodology: We searched electronic databases like MEDLINE, EMBASE, CINAHL, and Science Citation Index, checked documents and references, and contacted experts. We included WHO reported Corona diseases (COVID-19) situation reports from January 2020 to April 10, 2020 related to the diagnosis of COVID-19 diseases. Both reviewers independently screened titles and abstracts, assessed studies for inclusion, appraised quality, and extracted data.Result: Regular confirmation of COVID-19 was based on the detection of particular sequences of viral RNA by NAAT such as Polymerase chain reaction (PCR). Sensitivity was comparatively high in the first week. Serological assays are qualitative detection of IgM and IgG antibodies against SARS-CoV-2 in serum gave result within 2 to 10 minutes. The rapid antigen tests might be providing the advantage of fast time to results and low cost detection of human CoVs, however they were likely to suffer from reduced sensitivity based on the experience with this method for other respiratory viruses.Conclusion: Immunological assays are never goanna be better than molecular ones. May be molecular and immunological tests combined can be a good strategy.Bangladesh Journal of Infectious Diseases, April 2020;7(suppl_1):S11-S17